Mechanical and structural analysis of the pulmonary valve in congenital heart defects: A presentation of two case studies. (January 2019) - Sulejmani, Fatiesa; Pokutta-Paskaleva, Anastassia; Salazar, Olga; Karimi, Mohsen; Sun, Wei
Abstract: Objective: Congenital Heart Disease (CHD) is the leading cause of pediatric mortality, with many cases affecting the right ventricular outflow tract (RVOT) or pulmonary valve (PV). Understanding the mechanics of the disease condition can provide insight into development of durable repair techniques and bioengineered replacement devices. This work presents a mechanical and structural analysis of the pulmonary valve of two pediatric cases. Methods: Two PV tissues were excised as part of the operative procedure. One PV was obtained from a 9-month-old with Noonan syndrome (Patient 1) and the other from a 6-month-old with tricuspid atresia (Patient 2). The leaflets were subjected to planar biaxial tensile testing and second harmonic generation (SHG) imaging for mechanical and structural evaluation. Results and discussion: Patient 1 exhibited a more anisotropic mechanical response than Patient 2, with sample stiffness on par with that of adult PV tissue. Additionally, both samples showed radial and circumferential alignment of collagen fibers on the ventricularis and fibrosa sides of the leaflets, respectively. Collagen fibers on the fibrosa side were also more crimped than on the ventricularis side.